Smart Control of Expenses Using Mobile Devices - F. Junior, Giovani R.; Amorim, Vicente J. P.; Gomes, Thiago L.; Pereira, Igor M. (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2016: Anais do XLIII Seminário Integrado de Software e Hardware, 2016)
It is estimated that only 3.1% of the Brazilian population controls their expenses through digital applications. While 8.9% does not use a digital platform due to a lack of knowledge, 8.1% do not have time. Considering the current usage levels, applications providing a more automated control of expenditures would simplify this task for an average user, making mobile applications a more attractive option. Using digital image processing techniques, optical character recognition (OCR), and post-processing a novel software was developed in Android for receipts automatic recognition allowing mobile users to monitor expenses using photos. Information recognized by the application replicated a real receipt with an acceptable level of similarity.